Resistant [compact disc, unabridged] - Palmer, Michael, 1942-2013 (Macmillan Audio, 2014)
When Dr. Lou Welcome fills in last minute for his boss at a national conference in Atlanta, he brings along his best friend, Cap Duncan. But an accident turns tragic when Cap injures his leg while running. The open wound is the perfect breeding ground for a deadly microbial invader committed to eating Cap alive from the inside out. Turning to the Centers for Disease Control, Lou uncovers a link to a shadowy group known as One Hundred Neighbors who are using health institutions as hostages.